SURABAYA’S STRATEGY TOWARDS GREEN CITY - Erichawati, Zunita; Pramono, Sapto; Roekminiati, Sri; Lestari, Damajanti Sri (Proceeding of International Conference on Multidisciplinary Research, 2024)
Surabaya, as the second largest city in Indonesia with a population of 3,095,026 in 2019, faces significant challenges related to population growth, which has resulted in an increased demand for land for infrastructure development and supporting facilities. While this demand is important to meet the needs of citizens, it also creates new problems such as environmental pollution in the form of water, air, and soil, as well as disaster risks such as floods and droughts. One of the environmental impacts felt is the increasingly noticeable temperature change. Therefore, to respond to these challenges, the Surabaya City Government is taking steps towards the Green City concept. The main goal is to realize a sustainable and environmentally friendly city. The main focus of this article is to analyze Surabaya City's efforts in implementing the Green City concept by focusing on the provision of Green Open Space (RTH). The research method used is a literature study using secondary data from various sources such as books, theses, journal articles, papers, and related electronic sources. The results showed that the Surabaya City Government has tried to fulfill three initial attributes towards Green City, namely sustainability-based planning and design, development of extensive Green Open Space, and encouraging the development of green communities and buildings. These efforts show concrete steps in responding to environmental challenges and realizing an environmentally sound city in the midst of rapid urban growth.